A Systematic Literature Review on the Effectiveness of the Merdeka Curriculum in Enhancing Student Competencies - Siti Melasari; Bela Ayu Permatasari; Muhammad Hanafi; Selnistia Hidayani (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study aims to evaluate the effectiveness of the Merdeka Curriculum in enhancing student competencies through a systematic literature review of 28 selected articles published between 2020 and 2025. The review followed the PRISMA framework, involving identification, screening, eligibility assessment, and final inclusion stages. Data were synthesized using a structured extraction table to analyze research objectives, methods, findings, and relevance to the Merdeka Curriculum. The results indicate that the curriculum supports more flexible, differentiated, and project-based learning, contributing to improvements in creativity, independence, and higher-order thinking skills. Several studies also highlight increased student engagement and the development of the Pancasila Student Profile as central outcomes of the curriculum's implementation. However, challenges persist, including varied teacher readiness, limited learning resources, and inconsistent school-level support, which influence the curriculum's overall effectiveness. The discussion emphasizes that while the Merdeka Curriculum holds strong potential to transform learning, its success depends on systemic factors such as professional development, resource availability, and administrative commitment. The study concludes that the curriculum offers a promising framework for modern education but requires strengthened implementation strategies to achieve its intended impact across diverse educational settings